PENGARUH PELATIHAN KERJA TERHADAP KINERJA KARYAWAN DI KANTOR PEMADAM KEBAKARAN KABUPATEN SIDENRENG RAPPANG - Sumitro Bachtiar; Gazali Amin; Dian Nirmasari (PIRSAP (Paser Institute for Scientific Research and Publications), 2026)
This study aims to determine the effect of job training on employee performance at the Fire Department Office of Sidenreng Rappang Regency. The research employed a descriptive quantitative method, with a population of 150 employees. The sample was determined using the Slovin formula, resulting in a total of 35 respondents. Data analysis techniques used in this study included validity and reliability tests, classical assumption tests, and simple linear regression analysis. The results of the t-test showed a significance value of 0.000, which is below the significance level of α = 0.05, indicating that job training has a positive and significant effect on employee performance. Furthermore, the coefficient of determination (R²) test revealed that job training contributes 21.5% to employee performance, while the remaining 78.5% is influenced by other variables not examined in this study. Based on these findings, it can be concluded that job training is an important factor in improving employee performance in the organization.